PENGARUH KERAPATAN POPULASI PAKCOY (Brassica rapa L.) PADA HIDROPONIK SISTEM RAKIT APUNG - Sodikin, Erizal; Harun, M. Umar; Negara, Zaidan P.; Afrizal, Jeri (Badan Penelitian dan Pengembangan Daerah KabupatenMuara Enim, 2022)
The research was on Saung Hydoponic Bedeng Putih Indralaya from April until June, 2022. The purpose of the study was to determine the best spacing for pakcoy cultivation in hydroponic floating systems. The research activited carried out included installing mulch on styrofoam, seeding seeds, transplanting, observing plant, providing AB mix nutrition, checking ppm, pH, and water temperature, controlling pests and diseases plants, cleaning weeds in hydroponic areas, and harvesting. Pakcoy cultivation on styrofoam measuring 1.5 m x 0.5 m in pond the area 9 m x 1.5 m. Based on observations, cultivation of pakcoy in floating systems the spacing of 25 cm x 20 cm or 10 plants in styrofoam resulted in the plant height of 26.60 cm, number of leaves were 18 , canopy area was 28.75 cm², fresh weight of plant was 210.40 g, and the percentage of plants worth selling was 100%.